GANTI KERUGIAN TERHADAP ANAK KORBAN TINDAK PIDANA PENCABULAN - Wahyudi; Fakhria, Sheila (JURNAL RISET INDRAGIRI, 2023)
Regulations in force in Indonesia have protected the rights of child victims of abuse. However, law enforcement officials often believe that punishing perpetrators with criminal penalties is the best approach to help victims and not by violating victims' rights, especially the right to compensation. Normative legal research methods were used in this study with a normative juridical approach and qualitative descriptive data analysis. The results showed that compensation for child victims of abuse was paid procedurally. Therefore, the provision of compensation is difficult because it requires the request of victims which is considered to have come first. The lack of support from the community and victims' legal representatives is a challenge for the Witness and Victim Protection Agency in assisting child molesters to get compensation. The right to redress has not been effective due to a lack of support from human resources, especially psychologists, in assisting victims of sexual violence and law enforcement officials. The lack of coercive action against perpetrators of sexual violence regarding the payment of compensation decided by the court, and the provision of compensation depending on the good intentions of the perpetrators, presents challenges for law enforcement officials in carrying out compensation to victims of sexual violence. In addition, it must be requested first and the court has the authority to reject the request for compensation of the child victim, then this right is not fundamental. Restitution cannot be considered a right, because if it is, it must be granted automatically